Distributed Control with Web-based 3D Visualization using Kinematics Analysis for IoRT - Z Iklima, T M Kadarina (Journal of Engineering and Scientific Research, 2020)
The use of graphical user interface in web platform has been increasing in the recent decades. The concept of Internet of Robotic Things (IoRT) integrates heterogenous intelligent devices into a distributed architecture of platforms. This research is conducted to deliver proof of concept of distributed control of 2 DOF robot manipulator with web-based 3D visualization. The 3D modeling was developed using Three.js and the WebGL library. Synchronization was made using WebSocket communication on TCP network layer. This protocol allowed 3D mesh data broadcasted from web interface to manipulator with average response 7.86 ms. Moreover, using Denavit-Hartenberg convention, kinematic model facilitates the convention of end-effector position data into angular form and vice versa. The error percentage at a joint 1 is 4% and joint 2 of 2.96%. The error occurs because of the characteristic of inverse function called singularity in which the application value in each joint has the input values of and respectively to get the end-effector position on the 2 DoF Manipulator Robot.